EFFECT OF ORAL INTAKE OF MICROPLASTIC ON THE CHANGES IN NEPHRON STRUCTURE AMONG MALE WISTAR RATS - Priskilla Naomi Palyama; Yudhiakuari Sincihu; Irene Lingkan Parengkuan (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Introduction: Microplastic bioaccumulation in nephron tissue can cause high levels of nephron mitochondrial reactive oxygen species, endoplasmic related stress proteins and inflammation-related proteins.Material and methods: This study observed damage to the tubular and glomerular structures of experimental animals due to oral intake of microplastics. 46 Wistar rats used were divided into one control(C)  and five experimental groups (Xn). The experimental group was exposed to low-density polyethylene microplastic doses of 0.0375 mg, 0.075 mg, 0.15 mg, 0.3 mg and 0.6 mg daily for 90 days with the probe, respectively. Damage to the tubular and glomerular structures was observed through microscopic examination of the preparations stained with hematoxylin eosin.Results: The results of One-Way ANOVA test showed a significant difference between groups with tubular damage (p <0.05). Meanwhile, the results of Kruskal Wallis test showed a significant difference between groups with glomerular damage (p <0.05).Conclusion: Multiple comparation indicated that exposure to microplastic started at 0.0375 mg daily had led to damage to the tubular and glomerular. Ingestion of microplastic particles causes renal tubular and glomerular damage in Wistar rats.